Teaching Science with Context Historical, Philosophical, and Sociological Approaches (Science: Philosophy, History and Education,, 2018)
This book offers a comprehensive overview of research at interface between History, Philosophy and Sociology of Science (HPSS) and Science Teaching in Ibero-America. It contributes to research on contextualization of science for students, teachers and researchers, and explains how to use different episodes of history of science or different themes of philosophy of science in regular science classes through diverse pedagogical approaches. The chapters in this book discuss a wide range of topics under different methodological, epistemological and didactic approaches, reflecting the richness of research developed in Spanish and Portuguese speaking countries, Latin America, Spain and Portugal. The book contains chapters about historical events, topics of philosophy and sociology of science, nature of science, applications of HPSS in the classroom, instructional materials for students and teacher training courses and curriculum. This book provides a remarkable collection of studies in HPSS and science education. This collection also serves as an impressive demonstration of the scholarly richness in the Ibero-American communities and is certainly useful both for researchers as well as for educators. Prof. Dr. Peter Heering, Europa Universität Flensburg, Germany A comprehensive and illuminating collection of 26 Latin-American HPS&ST research papers. Contributors manifest a solid knowledge of history, philosophy, and sociology of science, and of international research linking these fields to theoretical, curricular, and pedagogical issues in science teaching and in teacher education. Professor Michael R. Matthews, University of New South, Sydney, Australia The worldwide interest in the uses of history, philosophy, and sociology of science to foster science education is also present in Latin and Iberian countries. This book presents the state of the art of this interest. These theoretical and empirical studies deal with the complexities of these issues. Olival Freire Jr., Instituto de Física - Universidade Federal da Bahia (UFBA), Salvador, Brazil An essential volume for all science educators. Comprehensive and full of valuable commentary. For initiates, this volume effectively introduces the role of history, philosophy and sociology of science in teaching, from its philosophical and cultural foundations to samples of classroom practice. For exerienced educators, it offers substantial enrichment, from addressing misconceptions to teacher education to the challenges of assessment. By bridging former language barriers, this impressive collection allows educators from around the world to benefit from the rich experience of its contributors in Latin America. Douglas Allchin, University of Minnesota, St. Paul, USA.